Penerapan Media Video Pembelajaran Kompetensi Membuat Desain Blus Sesuai Konsep Kolase terhadap Hasil Belajar Siswa Kelas XI SMK Cendika Bangsa Malang - Ayunda Salsadilla; Deny Arifiana; Marniati Marniati; Mein Kharnolis (Departement of Mathematics Education, 2024)
Learning Videos are one of the media that teachers can use to help achieve effectiveness and efficiency in learning. The aim of this research is to describe the implementation of learning to make blouse designs according to the collage concept, to describe students responses to the application of learning video media for making blouse designs according to the collage concept, and to describe student learning outcomes after the application of learning video media. This is pre-experimental research with quantitative descriptive data analysis. The research subjects were 12 students of class XI Fashion Design at SMK Cendika Bangsa Malang. The data collection methods used are observation, questionnaires and assessment tests. The results of the research showed that the application of learning using video media was in a good category, the result of student observations were in the very good category, and the student responses were in the very good category. Student learning outcomes using video tutorial media reach completeness in the complete category.